How consumption expenditure and export can affect Malaysia economic growth - Zainol Abidin, Noorazeela; Abdullah, Nuraini; Saraih, Ummi Naiemah; Musaddad, Hafirda Akma (Universiti Teknologi MARA, Kedah, 2025)
Consumption expenditure and exports both play pivotal roles in influencing Malaysia's economic growth, but each presents distinct challenges. Consumption expenditure drives domestic demand, stimulates economic activity, and supports business growth. However, excessive reliance on consumption can lead to inflationary pressures and increased trade deficits if not balanced by domestic production. Additionally, high levels of consumer debt could undermine economic stability. On the other hand, exports are essential for Malaysia’s economy. This study examines the influence of consumption expenditure and exports on Malaysia's economic growth between 1990 and 2019. This research employed the autoregressive distributed lag (ARDL) technique. The primary results of this study indicate a favourable and substantial correlation between consumption expenditure and exports with regards to longterm economic growth. Exports are the sole factor that has a notable and positive impact on economic growth in the short term. It is crucial to regularly examine the effects of consumption expenditure and export performance on economic growth. Policymakers should maintain a high degree of adaptability and responsiveness, making necessary policy adjustments to address emerging economic issues and capitalise on opportunities. This involves careful management of both domestic demand and export